Natural disasters, public spending, and creative destruction: A case study of the Philippines - Shikha Jha; Arturo Martinez; Pilipinas Quising; Zemma Ardaniel; Limin Wang (Asian Development Bank Institute (ADBI), 2018)
Typhoons, floods, and other weather-related shocks can inflict suffering on local populations and create life-threatening conditions for the poor. Yet, natural disasters also present a development opportunity to upgrade capital stock, adopt new technologies, enhance the risk-resiliency of existing systems, and raise standards of living. This is akin to the "creative destruction" hypothesis coined by economist Joseph Schumpeter in 1943 to describe the process where innovation, learning, and growth promote advanced technologies as conventional technologies become outmoded. To test the hypothesis in the context of natural disasters, this paper takes the case of the Philippines - among the most vulnerable countries in the world to such disasters, especially typhoons. Using synthetic panel data regressions, the paper shows that typhoon-affected households are more likely to fall into lower income levels, although disasters can also promote economic growth. Augmenting the household data with municipal fiscal data, the analysis shows some evidence of the creative destruction effect: Municipal governments in the Philippines helped mitigate the poverty impact by allocating more fiscal resources to build local resilience while also utilizing additional funds poured in by the national government for rehabilitation and reconstruction.
Keywords: H72; H75; H76; O53; Q54; R11; 330; natural disasters; typhoons; poverty; household income mobility; development opportunity; foreign aid; fiscal transfers; municipalities; public spending; creative destruction; Asia; Philippines